2023
DOI: 10.3390/ijms24108650
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction: At the Nexus between Alcohol-Associated Immunometabolic Dysregulation and Tissue Injury

Abstract: Alcohol misuse, directly or indirectly as a result of its metabolism, negatively impacts most tissues, including four with critical roles in energy metabolism regulation: the liver, pancreas, adipose, and skeletal muscle. Mitochondria have long been studied for their biosynthetic roles, such as ATP synthesis and initiation of apoptosis. However, current research has provided evidence that mitochondria participate in myriad cellular processes, including immune activation, nutrient sensing in pancreatic β-cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 188 publications
0
6
0
Order By: Relevance
“…Mitochondria are critical sites of bioenergetics, fat oxidation, intermediary metabolism, apoptosis, mitophagy, and redox homeostasis [ 90 93 ]. They are one of the primary sources of oxidative stress involved in fatty liver diseases [ 94 ]; α-ketoglutarate dehydrogenase and pyruvate dehydrogenase are involved in redox reactions to generate NADH and FADH 2 in the tricarboxylic acid (TCA) cycle [ 95 ], then in the electron transport chain (ETC), complexes I, II, and III perform redox reactions to generate ATP [ 18 ]. Thus, to balance out the ROS/RNS generated from these redox reactions, many mitochondrial antioxidants and enzymes exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria are critical sites of bioenergetics, fat oxidation, intermediary metabolism, apoptosis, mitophagy, and redox homeostasis [ 90 93 ]. They are one of the primary sources of oxidative stress involved in fatty liver diseases [ 94 ]; α-ketoglutarate dehydrogenase and pyruvate dehydrogenase are involved in redox reactions to generate NADH and FADH 2 in the tricarboxylic acid (TCA) cycle [ 95 ], then in the electron transport chain (ETC), complexes I, II, and III perform redox reactions to generate ATP [ 18 ]. Thus, to balance out the ROS/RNS generated from these redox reactions, many mitochondrial antioxidants and enzymes exist.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, in the second line of defense, mitochondria trigger mitophagy to restore redox homeostasis and retain the function of other mitochondria and organelles for cellular activities [ 101 ]. However, these natural lines of defense in mitochondria can be altered after excessive consumption of or exposure to alcohol (ethanol) [ 85 , 94 ], drugs [ 66 , 102 , 103 ], viruses [ 104 ], and some nutrients, including fructose [ 105 ]. Specifically, these exposures can alter mitochondrial redox homeostasis and oxidatively damage DNA [ 106 , 107 ], RNA [ 106 ], lipids, and proteins, through PTMs [ 8 , 26 , 48 , 70 , 108 , 109 ], causing inactivation of their functions and signaling pathways, leading to mitochondrial dysfunction [ 26 , 53 , 68 , 83 ], death of hepatocytes, and liver damage [ 17 , 110 ] or age-related conditions [ 91 , 111 113 ].…”
Section: Introductionmentioning
confidence: 99%
“…The liver plays a crucial role in maintaining immune tolerance to self-antigens while effectively responding to pathogenic challenges [ 20 ]. However, dysregulation of immune responses can lead to liver diseases, including autoimmune liver diseases and liver injury [ 21 ]. Antigen-presenting cells (APCs), particularly macrophages, assume a pivotal role in the immune response and tissue repair processes in ALF [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as the major organ involved in metabolism of alcohol, the liver contains plenty of mitochondria for energy production via oxidation of multiple substrates, thus is specifically susceptible to damage from alcohol consumption . Previous studies have shown that chronic alcohol administration was able to impair the ultrastructure and molecular dynamics of mitochondria, as well as the activity of respiratory chain complexes and synthesis of adenosine 5′-triphosphate (ATP) . Meanwhile, the mitochondrial oxidative phosphorylation (OXPHOS) was also interfered by alcohol via inhibiting the synthesis of proteins of the electron transport chain and the ATP synthase .…”
Section: Introductionmentioning
confidence: 99%
“…5 Previous studies have shown that chronic alcohol administration was able to impair the ultrastructure and molecular dynamics of mitochondria, as well as the activity of respiratory chain complexes and synthesis of adenosine 5′-triphosphate (ATP). 6 Meanwhile, the mitochondrial oxidative phosphorylation (OXPHOS) was also interfered by alcohol via inhibiting the synthesis of proteins of the electron transport chain and the ATP synthase. 7 Conversely, mitochondrial damage of the liver will be doomed to energy dysbolism and enhances ROS formation.…”
Section: Introductionmentioning
confidence: 99%